2013
DOI: 10.1016/j.celrep.2013.02.027
|View full text |Cite
|
Sign up to set email alerts
|

UBXN1 Interferes with Rig-I-like Receptor-Mediated Antiviral Immune Response by Targeting MAVS

Abstract: SUMMARY RNA viruses are sensed by RIG-I-like receptors (RLRs), which signal through a mitochondria-associated adaptor molecule, MAVS, resulting in systemic antiviral immune responses. Although RLR signaling is essential for limiting RNA virus replication, it must be stringently controlled to prevent damage from inflammation. We demonstrate here that among all tested UBX-domain-containing protein family members, UBXN1 exhibits the strongest inhibitory effect on RNA-virus-induced type I interferon response. UBXN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 51 publications
4
60
1
Order By: Relevance
“…This finding has been corroborated by more recent work that has uncovered a second TRAF3 binding site in MAVS corresponding to this same region [92]. In fact, a more recent study has reported that an ubiquitin regulatory X domain-containing protein (UBXN1) also negatively regulates MAVS by binding it and blocking its interaction with TRAF3/TRAF6 at the C-terminal binding site, further supporting the importance of this region in MAVS-mediated signaling [54]. Work is ongoing to determine the specific kinases responsible for the primary phosphorylation of MAVS that facilitates PLK1 binding.…”
Section: Mavs Regulation At the Mitochondrial Membranesupporting
confidence: 61%
“…This finding has been corroborated by more recent work that has uncovered a second TRAF3 binding site in MAVS corresponding to this same region [92]. In fact, a more recent study has reported that an ubiquitin regulatory X domain-containing protein (UBXN1) also negatively regulates MAVS by binding it and blocking its interaction with TRAF3/TRAF6 at the C-terminal binding site, further supporting the importance of this region in MAVS-mediated signaling [54]. Work is ongoing to determine the specific kinases responsible for the primary phosphorylation of MAVS that facilitates PLK1 binding.…”
Section: Mavs Regulation At the Mitochondrial Membranesupporting
confidence: 61%
“…The UBX-domain-containing protein UBXN1 inhibited RNA virus-mediated antiviral signaling by binding to the MAVS protein, preventing oligomerization thereof (67). Further study showed that the Smad ubiquitin regulatory factor (Smurf) 2 negatively regulated antiviral type I IFN responses by interacting with the MAVS protein, triggering proteasome-mediated degradation (68).…”
Section: Mitochondrial Proteins and Innate Immunitymentioning
confidence: 99%
“…UBX domain-containing protein 1 (UBXN1) contains both the N-terminal UBA domain and the C-terminal UBX domain, and it was recently discovered to interfere with RIG-I-mediated antiviral immune response by targeting the mitochondrial antivirus-signaling protein (16). In this study, we used a small scale siRNA library that screened out UBXN1 as a negative regulator in TNF␣-triggered NF-B activation.…”
mentioning
confidence: 99%